Amidosquaramides – a new anion binding motif with pH sensitive anion transport properties. Issue 35 (22nd August 2022) - Marchetti, Luke A.; Krämer, Tobias; Elmes, Robert B. P.
Abstract : We report a family of amidosquaramides with pKa values close to physiological pH. Intramolecular H-bonding affects anion binding leading to moderate Cl − transmembrane transport at physiological pH, but under acidic conditions anion transport is effectively 'switched on'. Abstract : Stimuli responsive anion transport is becoming an important aspect of supramolecular anion recognition chemistry. Herein, we report the synthesis of a family of anion receptors that incorporate a new anion binding motif, amidosquaramides. We show using experimental and computational methods that these receptors have p K a values close to physiological pH but also display intramolecular H-bonding interactions that affect anion recognition. Moreover, moderate activity in a Cl − /NO3 − exchange assay is observed at physiological pH that can be effectively 'switched on' when repeated under acidic conditions. The reported findings provide synthetic methods that can be used for the construction of more complex squaramide based anion receptors and also provide insight into the importance of conformational analysis when considering receptor design.